Surface modification and performance enhancement of nano-hybrid f-MWCNT/PVP90/PES hemodialysis membranes - Irfan, Muhammad (Elsevier, 2014)
The use of nanoparticles for surface modification and performance enhancement of membranes is another latest trend in membrane technology. In this work acid functionalized multi wall carbon nanotubes (f-MWCNT) was initially mixed with polyvinylpyrrolidone (PVP) in dimethylformamide (DMF) to form nano-composites (NCs) and then blended with polyethersulfone (PES). The PES/PVP-f-MWCNT nano-hybrid hemodialysis membrane was formed via the phase inversion process. The membranes were characterized and their performances were then evaluated in terms of pure water permeation rates (PWP), urea, creatinine and lysozyme rejection. The results revealed that, compared to the pristine PES membrane, the PES nano-hybrid hemodialysis membranes were more hydrophilic; possess high PWP rate up to 72.20 L.m(-2).h(-1), exhibited 58.82% reduced protein absorption, and better uremic waste clearance of 56.30%, 55.08% and 27.90% of urea, creatinine and lysozyme respectively. Thus the addition of NCs in the membranes indeed modified the surface and enhanced the performance of the PES membranes.